Metaplasia Myelofibrosis - WIJAYANINGRUM, LENA; I DEWA MADE WIDI HERSANA; I KETUT TIRKA NANDAKA (Hang Tuah Medical Journal, 2025)
Background: Myelofibrosis with myeloid metaplasia is a rare myeloproliferative disorder. Epidemiological data on the incidence of Myelofibrosis with myeloid metaplasia are still lacking. In Goteborg, Sweden, from 1983 to 1992, the incidence of the disease was retrospectively calculated at 0.4 per 100,000 population. In population- based leukemia data in the UK, the incidence of Myelofibrosis with myeloid metaplasia is estimated to be 0.73 per 100,000 person-years in men and 0.40 per 100,000 person-years in women. It is estimated that there are 230 new cases each year in England and Wales, 330 in Italy, and 1,600 in the United States. No medical therapies have been shown to be effective against the overall survival of patients. The prognosis of myelofibrosis with myeloid metaplasia varies widely. For this reason, it is necessary to report cases of Myelofibrosis Myeloid Metaplasia Methode: Descriptive research, in the form of case reports of patients with myelofibrosis metaplasia, with data obtained from primary data anamnesa and direct physical examination of patients and secondary data from medical records, the results of examinations of doctors at RSPAL Dr Ramelan Surabaya 2022-2024. Results: Since 13 December 2022 until this date 3 May 2024 (17 months).Patient with a diagnosis of Primary Myelofibrosis and high Uric Acid after undergoing therapy with jakavi 15 mg 1x1. Allopurinol 300mg 1x1 and Nabic 3x1. Experienced improvement in complaints of increased appetite. Resting at night there are no complaints. Activity such as walking is not easily tired, mass in the abdomen that does not cause pain. On physical examination, there was an increase in body weight from 50 kg to 55 kg and still found S IV splenomegaly, from the haematological examination there was a decrease in platelets 136.00 (10^3µL) which was previously 203.00 (10^3µL). Uric acid improved from 10.8 mg/dl to 7.7 mg/dl. Conclusion: Jakavi is a drug containing ruxolitinib that can treat splenomegaly or disease-related symptoms in adult patients with myelofibrosis. Keywords: Myelofibrosis Metaplasia.Splenomegaly.Jakavi